CCL18 aggravates atherosclerosis by inducing CCR6-dependent T-cell influx and polarization - Singh, Anjana; Kraaijeveld, Adriaan O.; Curaj, Adelina; Wichapong, Kanin; Hammerich, Linda; de Jager, Saskia C. A.; Bot, Ilze; Atamas, Sergei P.; van Berkel, Theo J. C.; Jukema, J. Wouter; Comerford, Iain; McColl, Shaun R.; et al. (Frontiers in Immunology, 2024)
The CC chemokine ligand 18 (CCL18) is a chemokine highly expressed in chronic inflammation in humans. Recent observations of elevated CCL18 plasma levels in patients with acute cardiovascular syndromes prompted an investigation into the role of CCL18 in the pathogenesis of human and mouse atherosclerosis. CCL18 was profoundly upregulated in ruptured human atherosclerotic plaque, particularly within macrophages. Repeated administration of CCL18 in Western type diet-fed ApoE-/- mice or PCSK9mut overexpressing WT mice led to increased plaque burden, enriched in CD3+ T-cells. In subsequent experimental and molecular modeling studies we identified CCR6 as a functional receptor mediating CCL18 chemotaxis, intracellular Ca2+ flux, and downstream signaling in human Jurkat and mouse T-cells. CCL18 failed to induce these effects in vitro in murine spleen T-cells with CCR6 deficiency. The ability of CCR6 to act as CCL18 receptor was confirmed in vivo in an inflammation model, where subcutaneous CCL18 injection induced profound focal skin inflammation in WT but not CCR6-/- mice. This inflammation featured edema and marked infiltration of various leukocyte subsets, including T-cells with a Th17 signature, supporting CCR6's role as a Th17 chemotactic receptor. Notably focal overexpression of CCL18 in plaques was associated with an increased presence of CCR6+ (T) cells. Our studies are the first to identify the CCL18/CCR6 axis as a regulator of immune responses in advanced murine and human atherosclerosis.